2020
DOI: 10.1002/ddr.21661
|View full text |Cite
|
Sign up to set email alerts
|

β‐Glucuronidase‐ and OATP2B1‐mediated drug interaction of scutellarin in Dengzhan Xixin Injection: A formulation aspect

Abstract: Scutellarin is the major and active constituent of Dengzhan Xixin Injection (DZXX), a traditional Chinese medicine prepared from the aqueous extract of Erigeron breviscapus and widely used for the treatment of various cerebrovascular diseases in clinic. In present study, the possible pharmacokinetic differences of scutellarin after intravenous administration of scutellarin alone or DZXX were explored. Additional, the potential roles of β‐glucuronidase (GLU) and OATP2B1 in drug–drug interaction (DDI) between sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…DZXX was approved by the State Drug Administration in 2001. Pharmacological studies indicated that breviscapin in DZXX could reduce platelet damage, improve in vivo activity and exert neuroprotective effect (Li et al, 2017a;Shi et al, 2020). The scutellarin in DZXX have anti-inflammatory effects by blocking the expression of inflammatory genes (e.g., TNF-α, IL-6, NF-κB) (Lin et al, 2019) and inhibiting the TLR4/ NF-κB signaling pathway (Zhang et al, 2017).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…DZXX was approved by the State Drug Administration in 2001. Pharmacological studies indicated that breviscapin in DZXX could reduce platelet damage, improve in vivo activity and exert neuroprotective effect (Li et al, 2017a;Shi et al, 2020). The scutellarin in DZXX have anti-inflammatory effects by blocking the expression of inflammatory genes (e.g., TNF-α, IL-6, NF-κB) (Lin et al, 2019) and inhibiting the TLR4/ NF-κB signaling pathway (Zhang et al, 2017).…”
Section: Sensitivity Analysismentioning
confidence: 99%